Absorptive carbon nanotube electrodes: Consequences of optical interference loss in thin film solar cells1. Issue 16 (28th April 2015) - Tait, Jeffrey G.; De Volder, Michaël F. L.; Cheyns, David; Heremans, Paul; Rand, Barry P.
<x xml:space="preserve">Abstract</x> Ultrasonically spray coated carbon nanotube electrodes attain sheet resistances as low as 3.4 Ω □−1 without post-deposition treatments. Organic solar cells achieve similar performance as those with silver electrodes, while simulations of other PV materials elucidate device design parameters.